Language and style of the contemporary poet El Rass: a peculiar artist in the Lebanese musical scenario - De Blasio, Emanuela (Anaquel de Estudios Árabes, 2021)
This research focuses on the linguistic analysis of texts taken from the production of the Lebanese rapper El Rass. After an excursus on the underground musical scenario in Lebanon, the work focuses on the language, themes and style of El Rass, the artist who gave birth to a new type of rap. His songs are characterized not only by rhyme, but also by a refined language, by cultural and social references and by a strong link with the Arab cultural tradition. The author favors Arabic, to the detriment of French or English, drawing on both the high register (Standard Arabic) and the low register (Lebanese Arabic) of the language. El Rass stands out, in style and language, from most of the Lebanese rappers and constitutes a particularly interesting case study.
Keywords: El Rass; Lebanese rap; Standard Arabic; Lebanese Arabic; Linguistics